149k views
5 votes
Solve the equation-5y-9=-(y-1)

User Kakkalo
by
5.0k points

2 Answers

5 votes

Answer:


-2 (1)/(2)

Explanation:

So, we have


-5y-9=-(y-1)
The first thing we need to do is distribute, which makes


-5y-9=-y+1

Then, we add 9 to both sides to get rid of the 9 on the left side of the equation, leaving -5y alone


-5y=-y+10

After that, we must remove the y on the right side by adding y to both
sides. Since y is defined as 1, unless said otherwise, we will be left with


-4y=10
Now, this is where it can get a little confusing. At this point, all that's left to do is divide -4y by 4, and 10 by 4, which will give us


(-4y)/(-4) = (10)/(-4)

y = (10)/(-4)

This should be the end of the equation, but we need to simplify it to get our final answer. Since 4 and 10 both share 2 as a common factor, we will use 2 to simplify our fraction, which leaves us with


-(5)/(2)

But we still aren't done! Since the numerator is a higher number than the denominator, this is considered an improper fraction, which means we must convert it into a mixed number fraction.

We take the devisor, in this case, 2, and divide it by 5.


-5 ÷
-2=-2
r1

This leaves us with 2, and a remainder of one. Since the denominator stays the same, this will leave us with a final answer of


-2(1)/(2)

User Xims
by
4.5k points
2 votes

As given by the question

There are given that the equation:


-5y-9=-(y-1)

Now,

Solve the above equation

So,


\begin{gathered} -5y-9=-(y-1) \\ -5y-9=-y+1 \\ -5y-9+y-1=0 \\ -4y-10=0 \end{gathered}

Then,


\begin{gathered} -4y-10=0 \\ -4y=10 \\ y=(10)/(-4) \\ y=-2.5 \end{gathered}

Hence, the value of y is -2.5.

User Bholben
by
5.1k points